Dose-response Curves in the Fibrin Plate Assay Fibrinolytic Activity of Proteases - Haverkate, F; Traas, D. W (Thrombosis and Haemostasis, 1974)
In the fibrin plate assay different types of relationships between the dose of applied proteolytic enzyme and the response have been previously reported. This study was undertaken to determine whether a generally valid relationship might exist.Trypsin, chymotrypsin, papain, the plasminogen activator urokinase and all of the microbial proteases investigated, including brinase gave a linear relationship between the logarithm of the enzyme concentration and the diameter of the circular lysed zone. A similar linearity of dose-response curves has frequently been found by investigators who used enzyme plate assays with substrates different from fibrin incorporated in an agar gel. Consequently, it seems that this linearity of dose-response curves is generally valid for the fibrin plate assay as well as for other enzyme plate bioassays.Both human plasmin and porcine tissue activator of plasminogen showed deviations from linearity of semi-logarithmic dose-response curves in the fibrin plate assay.